Urban Bangladesh, geographical studies - Islam, Nazrul, 1941-; Ahsan, Rosie Majid; University of Dhaka. Urban Studies Programme (Dhaka : Urban Studies Programme, Dept. of Geography, University of Dhaka, 1996)
Contributed articles.
Includes bibliographical references.
Keywords: Urbanization -- Bangladesh; Cities and towns -- Bangladesh